Image Processing, Support Vector Mechanism, and Genetic Algorithm –A hybrid technique to detect cancerous growth in Digital Mammograms - et. al, Dr Ramesh Shahabadkar (International Journal of Advanced Science and Technology, 2020)
Abstract: It is very important to detect any malignant growth in human body correctly. Many times it is seen that incorrect detection due to misleading results, has led to trauma amongst patients. First step in correct detection ofmalignant growth is image segmentation. Genetic Algorithms fitness formula helps to produce correct offspring for correct image segmentation. This paper aims to lessen the quantity of misclassified images depicting malignant cancerous growth. Image processing techniques such as enhancement of image is used for proper detection of lesion. As a part of pattern classification, support vector mechanism is applied as a tool to identify malignant tumors between differentsamples.